Shariah compliance hospitality design: a Malay Muslim oriented architecture - Abdul Majid, Noor Hanita; Denan, Zuraini; Abdullah, Fauziah Hanum; Mohd Noor, Mohd Syukri (Elsevier, 2015)
As a Malay Muslim architecture, the traditional houses suggest characteristics of Syariah compliant (SC) design. In addition, assimilation of traditional Malay architecture to the hospitality buildings is seen as an approach to promote cultural tourism. Hence, this research aims to investigate the influences of traditional houses on the design of hospitality buildings. The methodologies adopted are case studies and literature reviews. The study analyses the SC characteristics of the Malay houses, discusses the SC hotel requirements and review selected examples of SC hotels as case studies. The findings indicated that there are profound vernacular features which compliments Syariah.